„Finansowe Fair Play UEFA” jako nowoczesne narzędzie rozwoju futbolu zgodnie z regułami konkurencji UE - Woźniak, Filip, Wojciech (Kwartalnik Prawa Publicznego, 2016)
The following article raises an interesting and quite controversial issue of UEFA Financial Fair Play (FFP). In this paper, I focus on the origins of FFP and I also show its aims and shape. Furthermore, I analyzed so called “Striani case” (C-299/15). This case opened a discussion on FFP’s compatibility with EU law, especially with competition law. Finally, I show some numbers highlighting the success of FFP and look into the future of this regulations.